Aspek Pendukung Daya Serap Pembelajaran Siswa Sekolah Menengah Pertama yang Menerapkan Full Day School - Samrion Arthur Fiolentino; Prias Hayu Purbaning Tyas (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to identify the various aspects that support the learning absorption of junior high school students enrolled in a full-day school program. The research uses a descriptive method, with a sample of 65 students from SMP Negeri 1 Kalasan. The data collection technique employed was a questionnaire, followed by categorizing the items by calculating the total score, determining scales, and describing the results.Based on the responses provided by the students, it was found that 17 items, representing 46.15% of the responses, indicated that the supporting aspects of learning absorption were very high, with external factors playing a significant role. Among the external factors—family, school, and community environments—the family environment was most frequently selected by the students, resulting in the highest score. The supporting aspects of learning absorption indicated by 13 items, with a percentage of 53.85%, showed that the learning absorption aspect was high, with the highest contributing factor being the external community environment.The findings of this study show that the most influential supporting aspect in helping students achieve good learning absorption in a full-day school program is the external family environment. However, other supporting aspects also follow, such as the external community, internal physical and psychological factors, and the external school environment.